2018
DOI: 10.1002/chem.201706175
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Simulations of Water Adsorption and Activation on the (−201) β‐Ga2O3 Surface

Abstract: Density functional theory calculations are used to study the molecular and dissociative adsorption of water on the (-201) β-Ga O surface. The effect of adsorption of different water-like species on the geometry, binding energies, vibrational spectra and the electronic structure of the surface are discussed. The study shows that although the hydrogen evolution reaction requires a small amount of energy to become energetically favourable, the over potential for activating the oxygen evolution reaction is quite h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 111 publications
2
14
0
Order By: Relevance
“…Interestingly, β-Ga 2 O 3 appears to show a fundamental difference to other TSOs in that its surfaces usually exhibit upward band bending and near-surface electron depletion, although this is sensitive to their environmental and chemical processing histories. This is in contrast to the downward band bending and electron accumulation commonly observed at ZnO, , CdO, SnO 2 , and In 2 O 3 surfaces . This difference is surprising given that, on exposure to the atmosphere, the surfaces of β-Ga 2 O 3 and those of other TSOs are similarly terminated with an outer layer of hydroxyl groups formed from the dissociative adsorption of water. Upward surface band bending allows the relatively facile formation of highly rectifying Schottky contacts (SCs) to β-Ga 2 O 3 , , but makes the formation of high-quality ohmic contacts more difficult, , and may also impact other applications such as gas/biosensing and catalysis, for which a high near-surface electron density is beneficial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, β-Ga 2 O 3 appears to show a fundamental difference to other TSOs in that its surfaces usually exhibit upward band bending and near-surface electron depletion, although this is sensitive to their environmental and chemical processing histories. This is in contrast to the downward band bending and electron accumulation commonly observed at ZnO, , CdO, SnO 2 , and In 2 O 3 surfaces . This difference is surprising given that, on exposure to the atmosphere, the surfaces of β-Ga 2 O 3 and those of other TSOs are similarly terminated with an outer layer of hydroxyl groups formed from the dissociative adsorption of water. Upward surface band bending allows the relatively facile formation of highly rectifying Schottky contacts (SCs) to β-Ga 2 O 3 , , but makes the formation of high-quality ohmic contacts more difficult, , and may also impact other applications such as gas/biosensing and catalysis, for which a high near-surface electron density is beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in atmospheric conditions the bare (2̅01) surface interacts with water vapor resulting in a natural hydroxyl termination with H w /O w H w binding to surface O s /Ga s atoms (note: “w” indicates water and “s” indicates surface). , This produces two different hydroxyl species, i.e., Ga s –O w H w and O s –H w , with the former having a relatively weak acceptor-like character, while the latter has a stronger donor-like nature . As a result, hydroxylation of the (2̅01) β-Ga 2 O 3 surface produces a net increase in electronic charge resulting in a downward shift in band bending compared to the bare surface.…”
Section: Introductionmentioning
confidence: 99%
“…Behrens et al found that Co 1.5 Ni 0.5 Ga LDH showed an overpotential of 382 mV in 1 M KOH solution . Nener et al used density functional theory calculations to reveal that the over potential on the (−201) β‐Ga 2 O 3 surface is very high . Since the intrinsic OER activity of bare GaO x is very poor, which should not be the active site for OER.…”
Section: Resultsmentioning
confidence: 99%
“…The latter component is reduced on heating as the OH is desorbed with the total area of the O1s reducing by 3%. 35 There is a corresponding change in the Ga core level lineshape as the Ga-OH component is removed on heating. The binding energies of the core levels in this n-type semiconductor are therefore correlated with the surface composition which affects the surface electronic states and hence potential barrier.…”
Section: N-type B-ga 2 Omentioning
confidence: 99%